2021
DOI: 10.1002/mrc.5121
|View full text |Cite
|
Sign up to set email alerts
|

Efficient transfer of DNP‐enhanced 1H magnetization to half‐integer quadrupolar nuclei in solids at moderate spinning rate

Abstract: We show herein how the proton magnetization enhanced by dynamic nuclear polarization (DNP) can be efficiently transferred at moderate magic-angle spinning (MAS) frequencies to half-integer quadrupolar nuclei, S ≥ 3/2, using the Dipolar-mediated Refocused Insensitive Nuclei Enhanced by Polarization Transfer (D-RINEPT) technique, in which a symmetry-based SR4 2 1 recoupling scheme built from adiabatic inversion 1 H pulses reintroduces the 1 H-S dipolar couplings, while suppressing the 1 H-1 H ones. The use of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…In order to observe the Zn and S sites located near the surface of ZnS·DDA NPls, we also transferred the 1 H magnetization to 67 Zn and 33 S nuclei using the dipolar-mediated refocused INEPT scheme ( D -RINEPT) , and enhanced the signal using QCPMG detection along with DNP. ,, For the DNP-NMR experiments performed at 9.4 T and 105 K, the unpaired electrons were introduced in the sample by impregnating ZnS·DDA NPls with a solution of 13 mM TEKPol nitroxide biradicals in 1,1,2,2-tetrachloroethane (TCE).…”
Section: Resultsmentioning
confidence: 99%
“…In order to observe the Zn and S sites located near the surface of ZnS·DDA NPls, we also transferred the 1 H magnetization to 67 Zn and 33 S nuclei using the dipolar-mediated refocused INEPT scheme ( D -RINEPT) , and enhanced the signal using QCPMG detection along with DNP. ,, For the DNP-NMR experiments performed at 9.4 T and 105 K, the unpaired electrons were introduced in the sample by impregnating ZnS·DDA NPls with a solution of 13 mM TEKPol nitroxide biradicals in 1,1,2,2-tetrachloroethane (TCE).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely when the spin-1/2 nuclei are subject to large homonuclear dipolar interactions, like in the case of protons, recoupling reintroducing the |m| = 2 space component of the heteronuclear dipolar interaction, such as those based on SR4 1 2 symmetry 220 , are required since they suppress the contribution of homonuclear dipolar interactions to the first-order average Hamiltonian 239,244,245 . Furthermore, we have recently demonstrated that the efficiency of the D-RINEPT transfer from protons to half-integer quadrupolar nuclei can be improved by employing SR4 1 2 recoupling built from composite or adiabatic tanh/tan inversion pulses, continuous wave irradiation during the windows and composite 90° and 180° pulses on the 1 H channel [245][246][247] . These modifications limit the losses due to 1 H-1 H dipolar interactions and improve the robustness to rf field inhomogeneity.…”
Section: Between Spin-1/2 Isotopesmentioning
confidence: 99%
“…The latter is typically low in the case of a quadrupolar nucleus such as 43 Ca because a proper magnetization spin lock, required in CP, can be prevented by the time dependence of the quadrupolar interaction. A viable option to partially circumvent this issue is to use low radio frequency (RF) fields. In DNP NMR , applications, RF fields comprised between 0.8 and 20 kHz have been reported on quadrupolar nuclei for proton-to-quadrupolar nucleus CPMAS. In the case of 43 Ca, MAS-DNP NMR was successfully used by Lee et al to understand the chemical environment of hydroxyapatite by recording 1 H– 43 Ca dipolar-based 2D correlation spectra that enabled the distinction of core and surface Ca 2+ sites.…”
Section: Introductionmentioning
confidence: 99%